Recommendations for the Diagnosis, Prevention, and Control of Coronavirus Disease-19 in Children-The Chinese Perspectives - Feng Fang; Yu Chen; Dongchi Zhao; Tonglin Liu; Yongjian Huang; Liru Qiu; Yan Hao; Xiaolin Hu; Wei Yin; Zhisheng Liu; Runming Jin; Qin Ning; et al. (Frontiers Media S.A., 2020)
Ever since SARS-CoV-2 began infecting people by the end of 2019, of whom some developed severe pneumonia (about 5%), which could be fatal (case fatality ~3.5%), the extent and speed of the COVID-19 outbreak has been phenomenal. Within 2.5 months (by March 18, 2020) over 191,127 COVID-19 patients have been identified in 161 countries. By then, over 700 pediatric patients were confirmed to have COVID-19 in China, with only about 58 diagnosed elsewhere. By now, there are thousands of children and adolescents infected. Chinese pediatricians would like to share their experience on how these patients were managed in China and the key recommendations that had guided them in meeting the evolving challenges. A group of experts were summoned by the Chinese Pediatric Society and Editorial Board of Chinese Journal of Pediatrics to extract informative data from a survey on confirmed COVID-19 pediatric patients in China. Consensus on diagnosis, management, and prevention of pediatric COVID-19 were drawn up based on the analysis of such data plus insights gained from the past SARS and MERS coronavirus outbreaks. Relevant cumulating experiences from physicians managing adult patients, expedited reports on clinical and scientific COVID-19 and SARS-CoV-2 data, and the National Health Committee guidelines on COVID-19 management were integrated into this proposal.